2008
DOI: 10.14453/aabfj.v2i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social reporting practices of top Indian software firms

Abstract: This study examines the corporate social reporting practices and the motivations behind such practices of the top 16 software firms in India. The 2003-2004 annual reports were analysed using content analysis to examine social reporting relating to human resource and social relations, combined with 14 case study interviews that examined managerial motives behind corporate social reporting (CSR) relating to the sample firms. When findings were analysed using legitimation strategies, the results indicate that fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Narwal (2007) constructed the CSR disclosure index of 21 items with no specific themes for the sample of 33 public and private sector banks in Haryana and found that CSR activities are mainly focused on education, balanced growth, health, environmental marketing and customer satisfaction. Murthy and Abeysekera (2008) Uwuigbe et al (2011) constructed the CSRDI of 20 items, i.e., environment, energy, R&D, employee health and safety for the 30 selected companies listed in Nigerian stock exchange market and found the significant association between the level of CSR disclosures and the corporate environmental visibility. Kansal and Singh (2012) constructed the Corporate Social Environment Energy Emission Index (CSEEE Index) consisting of 96 items with seven sub-themes for the sample of 82 top public listed companies and suggested that companies should focus more on the environment, emissions, product, safety innovations and alternative usage of energy.…”
Section: Regulations On Csr -International and National (India)mentioning
confidence: 99%
“…Narwal (2007) constructed the CSR disclosure index of 21 items with no specific themes for the sample of 33 public and private sector banks in Haryana and found that CSR activities are mainly focused on education, balanced growth, health, environmental marketing and customer satisfaction. Murthy and Abeysekera (2008) Uwuigbe et al (2011) constructed the CSRDI of 20 items, i.e., environment, energy, R&D, employee health and safety for the 30 selected companies listed in Nigerian stock exchange market and found the significant association between the level of CSR disclosures and the corporate environmental visibility. Kansal and Singh (2012) constructed the Corporate Social Environment Energy Emission Index (CSEEE Index) consisting of 96 items with seven sub-themes for the sample of 82 top public listed companies and suggested that companies should focus more on the environment, emissions, product, safety innovations and alternative usage of energy.…”
Section: Regulations On Csr -International and National (India)mentioning
confidence: 99%
“…Thus, their findings tend to be fragmented and incomparable. Murthy and Abeysekera (2008) argue that an examination of disclosure practices using a longitudinal approach would reveal possible variations in disclosure practices not evident in a cross-sectional study. We therefore undertake a longitudinal study.…”
Section: Introductionmentioning
confidence: 99%
“…Most businesses that report on ESG are expanding CSR investments in print management data volumes and over-reports. ESG's coverage is a tactic to affect a company's public perception and shape the way certain players perceive the company (Murthy & Abeysekera, 2008;Perks et al, 2013). Many companies see ESG reporting as a platform for public relations to build a good image and gain strong market reputation.…”
Section: The Challenges Of Esg Disclosurementioning
confidence: 99%